Estimating future consumption of forest chips based on insights from energy producers: a case study for Finland - Niinistö, Tuomas; Anttila, Perttu; Sikanen, Lauri; Kärhä, Kalle; Routa, Johanna (Taylor & Francis, 2025)
Forest chips have become a crucial energy source in Finland, largely driven by political decisions topromote renewable energy. This study examines trends in forest chip consumption in Finnish heat-only and combined heat and power plants, offering projections for 2026 and 2033 based on a surveyfor energy producers and the statistical data from 2023. The survey represented 79% of forest chipconsumption in 2023, while the remaining consumption was estimated using linear regressionanalysis. The findings suggest that forest chip consumption may increase from 11.0 to 11.4 million cubicmetres (Mm3, solid over bark) by 2026. The reduction in energy peat and fossil fuel use is likely todrive higher consumption of forest chips when electricity prices are high and electricity-basedheat generation becomes unprofitable. The growing role of wood as a regulating power may alsolead to increased roundwood burning as storage times lengthen. By 2033, consumption is expected to decrease to 9.7 Mm3, primarily due to the adoption ofalternative energy production technologies, such as utilisation of waste heat. No investments incarbon capture and storage were identified. As the availability of biogenic carbon remainssignificant, climate policy should prioritise the promotion of these technologies.
Keywords: renewable energy policy; climate policy; bioenergy; wood energy; energy transition; survey